2009
DOI: 10.1007/s10620-009-0728-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Proximal Neoplasms Among Asymptomatic Patients According to Distal Colorectal Findings

Abstract: Colorectal cancer has been described in association with hyperplastic polyposis. Only half of proximal colon cancers are associated with distal adenomas. To compare the prevalence of proximal and advanced neoplasia between patients with distal hyperplastic polyps only; with distal adenomas with or without hyperplastic polyps; and with no distal polyps, we retrospectively analyzed data of 1,064 adults who underwent colonoscopy. Of these patients, 3% had neoplasia. Proximal neoplasia occurred in 0.8% of 945 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 23 publications
0
3
0
2
Order By: Relevance
“…It remains controversial whether the incidence of proximal neoplasia increases with the findings of distal hyperplastic polyps, as studies have shown conflicting results [2,3,6,7]. In the current study, one patient with the incidental finding of a rectal adenomatous lesion was found to have several tubular adenomas and hyperplastic polyps on subsequent colonoscopy examination.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…It remains controversial whether the incidence of proximal neoplasia increases with the findings of distal hyperplastic polyps, as studies have shown conflicting results [2,3,6,7]. In the current study, one patient with the incidental finding of a rectal adenomatous lesion was found to have several tubular adenomas and hyperplastic polyps on subsequent colonoscopy examination.…”
Section: Discussionmentioning
confidence: 53%
“…The incidental findings of rectal polyps can be clinically significant, in terms of increased risk of neoplasia in the proximal colon and increased risk of high-grade dysplasia in the rectal polyp [2][3][4][5]. It remains controversial whether the incidence of proximal neoplasia increases with the findings of distal hyperplastic polyps, as studies have shown conflicting results [2,3,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Age and gender are interacting factors, with women younger than 50 years having a lower risk of proximal than distal neoplasia, while males in the same age group have a higher prevalence of distal than proximal neoplasia,16,65,72 women between 50 and 70 years showing an increasing incidence of proximal neoplasia compared to women of younger age,62,65,69 and gender differences diminishing after the age of 70 62. With respect to geographic region, it has been suggested that although Eastern populations have fewer incidences of isolated proximal neoplasia, lesions that are more likely distal,8,38,44,45,7376 and a 10-year delay in the incidence of colonic neoplasia,43 Western and Eastern populations are becoming increasingly comparable due to the Westernization of the Eastern lifestyle. Note that the existing information concerns prevalences.…”
Section: Commentmentioning
confidence: 99%
“…43,44 Επίσης, από μελέτες φαίνεται ότι η κολονοσκόπηση υπερτερεί της ορθοσιγμοειδοσκόπησης στην ανίχνευση των νεοπλασμάτων του πάχος εντέρου. 45,46 Περίπου το 50% των προχωρημένων νεοπλασμάτων (καρκίνος, αδενώματα >1cm, πολύποδες με λαχνωτά χαρακτηριστικά και υψηλού βαθμού δυσπλασία) εντοπίζονται εγγύς της αριστερής κολικής καμπής, σημεία μη ορατά στην ορθοσιγμοειδοσκόπηση και μάλιστα εν απουσία αδενωματώδων πολυπόδων στο άπο κόλον.…”
Section: κολονοσκόπησηunclassified
“…47 Όπως αναφέρθηκε όμως και προηγουμένως, ένας σημαντικός αριθμός νεοπλασμάτων του εγγύς τμήματος του πάχος εντέρου παρατηρούνται εν απουσία αλλοιώσεων στο άπω τμήμα αυτού οπότε και διαφεύγουν της διάγνωσης. 45,46 Εξέταση κοπράνων για μικροσκοπική αιμορραγία-Fecal Occult Blood Test…”
Section: ορθοσιγμοειδοσκόπησηunclassified